Pertanggungjawaban Pidana terhadap Pelaku Penjualan Daging Anjing Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 - I Made Bramastra De Putra; I Nyoman Gede Sugiartha; I Putu Gede Seputra (Fakultas Hukum, Universitas Warmadewa, 2021)
Dogs are one of the favorite and much-loved pets, but this does not prevent the illegal sale of dog meat as a food ingredient. Considering that there is no clear criminal sanction from the illegal sale of dog meat from the government, the research aims to examine the accountability of the perpetrators of selling dog meat from a consumer protection perspective and the criminal sanction for the perpetrator based on law. This research was conducted with a normative method with conceptual approach and statutory approach. From the result the researcher found that the perpetrator must be responsible to consumers based on the Consumer Protection Law Article 4 letter a, which guarantees the safety, comfort and security of consumption of goods and / or services, and the perpetrator may be subject to a maximum fine of 2 billion rupiah or a maximum imprisonment of 5 years for violating the provisions in Article 8 based on the consumer protection law article 62 paragraph 1.